Introduction—Beyond Retribution: An Integrated Approach to Restorative Justice - John Owen Haley (Washington University Journal of Law & Policy, 2011)
This volume focuses on restorative justice. Topics include victim-offender reconciliation programs (VORP), victim reparation, and the benefits of therapeutic justice on criminal offenders. Information is provided on how the effectiveness of deterrence measures increase when restorative justice programs are also offered.
Keywords: Restorative justice; Criminal justice administration; Reparation (Criminal justice); Reconciliation (Law); Punishment in crime deterrence; Deterrence (Administrative law)